Immunohistochemical Analysis of Prognostic Protein Markers for Primary Localized Clear Cell Renal Cell Carcinoma. (25th January 2013) - Weber, Thomas; Meinhardt, Matthias; Zastrow, Stefan; Wienke, Andreas; Fuessel, Susanne; Wirth, Manfred P.
<x xml:space="preserve">Abstract</x> Recurrence is not reliably predictable in localized clear cell renal cell carcinoma. Proteinmarkers could improve predictive accuracy. Tissue-microarrays from 132 patients with primary localized ccRCC were immunohistochemically analyzed for VHL, Ki67, p53, p21, survivin, and, for microvessel-density, UEA-1. Nuclear stainings of Ki67, p21, and survivin were significantly associated with disease-specific survival and increased predictive ability from 74% to 76%, 77%, and 78%, respectively in a multivariate model including T-stage and Fuhrman grade. A score-variable, combining Ki67-, p21-, and nS-staining identified a subset of patients with high risk of disease recurrence and increased predictive ability in the multivariate model to 84%.